2023
DOI: 10.1007/s13671-023-00385-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immune-Modulating Treatments for Dermatological Diseases on the Risk of Infection with SARS-CoV-2 and Outcomes Associated with COVID-19 Illness

Abstract: Purpose of Review Immune-modulating treatments are used in dermatology for a variety of conditions. The authors aim to review the data regarding the safety of these treatments during the COVID-19 pandemic, namely the risk of infection with SARS-CoV-2 and the outcomes associated with COVID-19-related illness. Recent Findings Several large-scale studies found no increased risk of COVID-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…We found that the pro-inflammatory TNFR1 pathway is critical for early viral control of SCV2 replication in mice and that pulmonary preconditioning with recombinant TNFα potently limits SCV2 viral titers in the lung. Of note, patients undergoing TNFα blockade as a long-term treatment for dermatological or rheumatic diseases showed no increase in hospitalizations or severe COVID-19 disease [107][108][109] . However, the impact on early control of viral replication is difficult to ascertain from such clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the pro-inflammatory TNFR1 pathway is critical for early viral control of SCV2 replication in mice and that pulmonary preconditioning with recombinant TNFα potently limits SCV2 viral titers in the lung. Of note, patients undergoing TNFα blockade as a long-term treatment for dermatological or rheumatic diseases showed no increase in hospitalizations or severe COVID-19 disease [107][108][109] . However, the impact on early control of viral replication is difficult to ascertain from such clinical studies.…”
Section: Discussionmentioning
confidence: 99%